Influence of business risk, company size and good corporate governance on company value - Tri Yulianto; Hadi Pramono; Azmi Firtiati; Amir Amir (Jurnal Mantik, 2024)
This research aims to determine and analyze the influence of business risk, company size, and good corporate governance on company value with profitability as a control variable in the non-cyclical consumer sector. The dependent variable in this research is company value, while the independent variables used in this research are business risk, company size, and good corporate governance and the control variable used in this research is profitability. The population of this research is all non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The sample selection in this study usedpurposive samplingwith certain criteria to obtain a sample of 14 companies. The data used is secondary data sourced fromannual report,Data analysis technique uses multiple linear regression analysis. The research results show that business risk, company size, institutional ownership, audit committee and ROA have no effect on company value. while managerial ownership has a negative effect on company value and an independent board of commissioners has a positive effect on company value. The implication that can be applied by companies is that if they want to increase company value they must pay attention to managerial ownership and an independent board of commissioners can also increase company value.